Silver Beach : a novel - Cox, Claire (Novelist) (University of Massachusetts Press, 2021)
It's been decades since Mara's family was last together, decades since the day her sister Allison drowned at Silver Beach. After the family tragedy, Mara's father took her to the opposite end of the country, where she made a tidy life for herself in western Massachusetts, with a good education, stable job, and loving girlfriend. Her half-sister, Shannon, was left behind with their mother in San Diego. Surviving on disability checks and handouts from family, Shannon can't remember a time when Linda wasn't drunk. When a heart attack lands Linda in the hospital, Shannon's first impulse is to skip town--to finally escape her mother's orbit and make her sister step up. While Mara gave up on Linda years ago and couldn't have less in common with her sister, an unemployed stoner, it's time for her to stop running from everything that makes her have feelings. This is a novel about the persistent, mystifying ties of family, the extravagant mess of addiction, and what it means to actually live inside your own life.